Listeria monocytogenes Meningoencephalitis and Cerebral Abscess in a Heart Transplant Recipient - Paul C. Adjei (Case Reports in Infectious Diseases)
A 54-year-old male, five months postorthotopic heart transplantation, presented with intermittent fevers, headaches, and “soupy” stools. Prior to presentation, he had low-level cytomegalovirus (CMV) viremia for two straight weeks. Given his immunosuppression, diarrhea, and low-level CMV viremia, he was presumed to have cytomegalovirus and/or C. difficile colitis and treated empirically for both on hospital day one. However, he developed neck pain/stiffness, diaphoresis, and worsening fevers on hospital day three. Blood cultures eventually grew Listeria monocytogenes; MRI of the brain with gadolinium showed left brain meningoencephalitis with early cerebral abscess formation. Lumbar puncture revealed elevated opening pressure, CSF neutrophilic pleocytosis, and elevated CSF protein and lactate but negative gram stain and cultures. First-line agent for Listeria meningoencephalitis is ampicillin. However, he reported amoxicillin allergy. Desensitization to ampicillin failed because ampicillin was too unstable per the allergist. He was therefore treated with penicillin monotherapy for eight weeks with complete resolution of his brain lesions and without any residual neurologic deficits.